Studies on Genetic Divergence in Cabbage Genotypes in the Mid Hills of Solan District, Himachal Pradesh, India - Seema Thakur; Sanjivni Pandey; Rajesh Thakur (Archives of Current Research International, 2024)
Cabbage (Brassica oleracea var. capitata L.) is one of the most important vegetables of the family Brassicaceae and is grown under temperate to tropical climatic conditions for its head in more than ninety countries throughout the world. The diversity in cabbage is immense due to the presence of variation in shape, size, weight and maturity of heads. The greater the variability in the available germplasm, more would be the chances for selecting superior genotypes for use in breeding programmes or direct use as cultivars. Twenty three genotypes of cabbage including check variety, Golden Acre were evaluated in a Randomized Complete Block Design (RCBD) with three replications. The results concluded that twenty-three diverse genotypes of cabbage were grouped into four clusters. The resultant four clusters showed genetic diversity and maximum number of genotypes were accommodated in cluster I (12) followed by II (7), IV (3) and III (1). The maximum inter cluster distance was recorded between cluster II and III, therefore, the hybridization between the genotypes of cluster II and III can be performed to get superior hybrids or recombinants in segregating populations for further breeding programmes. Based on the mean performance, genetic distance and clustering pattern, inter-varietal crosses can be made which may be advantageous in creating wider variability for better heterotic combinations and transgressive segregants in cabbage.